2021
DOI: 10.1093/ntr/ntab084
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns and Prevalence of Dual and Poly-Tobacco Use: A Systematic Review

Abstract: Introduction Improving understanding of the epidemiology of dual and poly-tobacco product use is essential for tobacco control policy and practice. The present study aimed to systematically review existing epidemiologic evidence on current dual and poly-tobacco use among adults globally. Methods We systematically searched online databases for studies published up to 30 June 2020. We included quantitative studies with measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Data source: (A) WHO report on the global tobacco epidemic, 2013 ( 5 ). (B) Chen et al ( 7 ). (C) The Tobacco Control Scale 2019 in Europe ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data source: (A) WHO report on the global tobacco epidemic, 2013 ( 5 ). (B) Chen et al ( 7 ). (C) The Tobacco Control Scale 2019 in Europe ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the consumption of conventional products such as cigarettes is slowly decreasing, novel nicotine and tobacco products such as e-cigarettes (vaping products) and heated tobacco products (HTPs) are gaining popularity in the European region since 2017, especially among the younger populations ( 3 ) and in the countries where the prevalence of conventional tobacco products is high ( 6 ). The proliferation of novel or alternative products in the market presents an opportunity for conventional smokers to use these products in combination with conventional ones, leading to dual or poly-product use ( 7 ). The 2020 Eurobarometer survey reports a great proportion of current “dual users” of e-cigarette users (59%) and heated tobacco product users (79%), using these products in addition to their current use of conventional products ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on patterns of multiple tobacco product use in U.S. adults has increased over the past decade [ 4 , 5 ]. In a systematic review of dual use and polyuse, eleven studies have presented prevalence estimates of dual use, and six studies have presented estimates of polyuse from 1992 to 2018 using data from nationally representative studies [ 5 ]. This review found that dual use and polyuse are becoming more common throughout the world, and that definitions of dual use and polyuse use have varied over time.…”
Section: Introductionmentioning
confidence: 99%
“…This review found that dual use and polyuse are becoming more common throughout the world, and that definitions of dual use and polyuse use have varied over time. Dual/polyuse is also higher among younger adults compared to older adults in the United States [ 5 , 6 ]. In addition, results from a recent study analyzing three nationally representative surveys for the years 2014–2016 reported that the most common adult dual use and polyuse groups in the United States were cigarettes and electronic nicotine delivery systems (ENDS) dual use (1.3–1.8%), and cigarettes, ENDS, and other combustibles (OC, i.e., cigars/cigarillos/little filtered cigars and traditional pipe/hookah) polyuse (0.2–0.7%) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…But for dual use, there are only few documents supporting additional risks, prolonged to nicotine and slow reductions. 4 Factors that make people to get addicted with tobacco include, mental illness (mental stress, depression, post-traumatic stress, schizophrenia, stress disorder etc. ), sadness of grief, impatience, frustrations, boredom, restlessness, anger and also just like that for craze and relaxing purposes.…”
mentioning
confidence: 99%